Transition from Tumor Tissue to Bone Marrow in Patients with Appendicular Osteosarcoma after Neoadjuvant Chemotherapy - Zhi-Ping Deng; Bao-Yue Liu; Yang Sun; Tao Jin; Bin Li; Yi Ding; Xiao-Hui Niu (Chinese Medical Journal, 2017)
Background: Limb-salvage surgery is the standard procedure for the treatment of appendicular osteosarcoma. Precise resection is the trend in limb-salvage surgery. The aim of this study was to evaluate a large series of cases to identify the histological relationship between the tumor and marrow and determine the intramedullary transition type and width from the tumor to normal marrow in patients with osteosarcoma after neoadjuvant chemotherapy. Methods: One hundred and six osteosarcoma specimens were evaluated. The tissue specimens were sectioned through the coronal axis by an electronic saw. The tissue was immersed in formalin solution for fixation and subsequently decalcified. The interface between the tumor and normal bone marrow was grossly determined and submitted for microscopic evaluation to detect the relationship between the tumor and bone marrow and identify the transition type and width. All histological slides were examined by experienced orthopedic pathologists. Results: Histologically, the interface between the tumor and normal bone marrow was classified into two patterns: “clear” and “infiltrated.” The clear pattern, characterized by a clear boundary between the tumor and marrow, was identified in sixty cases (56.6%). A subtype of the clear type, characterized by fibrous bands between the tumor and marrow, was found in 13 cases (12.3%). The infiltrated pattern, characterized by a boundary with tumor cell clusters embedded in the marrow, was found in 46 cases (43.4%). The infiltrating depth varied from 1 to 4 mm (mean, 2.6 ± 0.7 mm). No tumor cells were observed in the normal bone marrow areas next to the interface. Conclusions: The transition from osteosarcoma tissue to bone marrow after neoadjuvant chemotherapy can be divided into two histological patterns: clear and infiltrated. The greatest infiltration width was 4 mm from tumor to normal marrow in this study. This depth should be considered in the presurgical plan.